Research limitations and future directions on the effect of educational practice on the cultivation of teachers' professional competency of education major students: A case of M University in China - Jing, L.; Kamarudin, D.; Hu, X. (International Journal of Education and Knowledge Management, 2022)
A very important practical teaching activity for Chinese education major students during their four years of undergraduate study is educational practice. The process of education practice for education major students is a learning activity that will provide hands-on experience of the whole process of education and teaching practice, including participating in practical teaching of courses, classroom management, active learning and communication, relevant competitions, training and activities, etc. In this paper, a semi-structured interview questionnaire was used to interview relevant personnel at M University in China. The interviewees included eight instructors who were involved in the training of education majors and eight education graduates (currently primary and secondary school teachers) who had graduated for two to five years. The analysis of the interview results showed that: education practice of education major students can enhance education major students’ professional competence of teachers; education majors students’ education practice, training competitions and other activities in their four years of undergraduate study are beneficial to their career development. Therefore, strengthening education practice and training competitions for education major students has a positive impact on the cultivation of education major students, and universities where education major students are studying should broaden effective ways to strengthen links and cooperation with local governments and primary and secondary schools, education major students use their initiative, innovative educational practice training using smart education resources and more, so as to play an active role in cultivating more outstanding education major graduates.